HAb18G/CD147 promotes activation of hepatic stellate cells and is a target for antibody therapy of liver fibrosis - Zhang, Da-Wei; Zhao, You-Xu; Wei, Ding; Li, Ya-Lin; Zhang, Yang; Wu, Jiao; Xu, Jing; Chen, Changsheng; Tang, Hao; Zhang, Wei; Gong, Li; Han, Ying; et al. (Journal of hepatology, 2012)
Activated hepatic stellate cells (HSCs) located in the Disse’s space play a crucial role in liver fibrosis. HAb18G/CD147, a tumor-related glycoprotein, is highly expressed in hepatocellular carcinoma cells and fibroblasts. Whether HAb18G/CD147 plays an important role in the hepatic fibrogenesis is unknown. Immunohistochemistry for HAb18G/CD147 and α-smooth muscle actin expression in diseased liver tissues was used for correlation analysis. The function of HAb18G/CD147 in fibrogenesis was evaluated with the human HSCs LX-2 cell line and carbon tetrachloride-induced mouse liver fibrosis model. The specific antibody HAb18 targeting HAb18G/CD147 was injected intravenously into the mouse to investigate whether HAb18G/CD147 could be a potential target for liver fibrosis treatment. HAb18G/CD147 is highly expressed on activated HSCs in the sinusoid. The positive rates of HAb18G/CD147 expression in human HBV-related liver cirrhosis, liver biopsy with HBV and liver adjacent to hemangioma were 95.6% (65/68), 14.8% (8/54) and 6.4% (8/125), respectively. HAb18G/CD147 expression was significantly correlated with the Child–Pugh grade (r=0.2848, p=0.0186) and with the expression of α-smooth muscle actin in HSCs (r=0.4434, p=0.0002) in liver cirrhosis. Transforming growth factor-β1 upregulated HAb18G/CD147 expression in LX-2 cells. Transfection of HAb18G/CD147 promoted the profibrogenic genes expression. In mouse liver fibrosis model, HAb18G/CD147 expression increased with the development of fibrogenesis and decreased during the liver fibrosis spontaneous recovery. The HAb18 targeting HAb18G/CD147 could attenuate liver fibrosis. These data suggest that HAb18G/CD147 plays a role in HSC activation and is a potential therapeutic target in fibrosis/cirrhosis.